Biochar derived from olive oil pomace mitigates salt stress on seedling growth of forage pea - Gullap, Mehmet Kerim; Karabacak, Tuba; Severoglu, Sedat; Kurt, Ayse Nida; Ekinci, Melek; Turan, Metin; Aktas, Halit; Yildirim, Ertan (Frontiers in Plant Science, 2024)
Studies are being conducted to develop strategies to reduce the adverse effects of salinity stress.In the present study, it was aimed to determine the interactive effects of salinity stress with biochar on plant growth, the physiological and biochemical attributes of forage peas (Pisum sativum ssp. arvense L.). Salt applications were carried out with irrigation water at concentrations of 0, 25, 50, 75, and 100 mM NaCl. The experiment was conducted using a randomized complete block design with 3 applications (control: 0 (B0), 2.5% biochar (B1), and 5% biochar (B2)), 5 salt doses (0 (S0), 25 (S1), 50 (S2), 75 (S3), and 100 (S4) mM NaCl), and 3 replications, arranged in a 3x5 factorial arrangement. In the salt-stressed environment, the highest plant height (18.75 cm) and stem diameter (1.71 mm) in forage pea seedlings were obtained with the application of B1. The root fresh (0.59 g/plant) and dry weight (0.36 g/plant) were determined to be the highest in the B1 application, both in non-saline and saline environments. A decrease in plant chlorophyll content in forage pea plants was observed parallel to the increasing salt levels. Specifically, lower H2O2, MDA, and proline content were determined at all salt levels with biochar applications, while in the B0 application, these values were recorded at the highest levels. Furthermore, in the study, it was observed that the CAT, POD, and SOD enzyme activities were at their lowest levels at all salt levels with the biochar application, while in the B0 application, these values were determined to be at the highest levels.There was a significant decrease in plant mineral content, excluding Cl and Na, parallel to the increasing salt levels. The findings of the study indicate that biochar amendment can enhance forage peas growth by modulating the plant physiology and biochemistry under salt stress.Considering the plant growth parameters, no significant difference was detected between 2.5% and 5% biochar application. Therefore, application of 2.5 biochar may be recommended.